6x-6+2(2x+6)=-4(x+3)

Simple and best practice solution for 6x-6+2(2x+6)=-4(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-6+2(2x+6)=-4(x+3) equation:


Simplifying
6x + -6 + 2(2x + 6) = -4(x + 3)

Reorder the terms:
6x + -6 + 2(6 + 2x) = -4(x + 3)
6x + -6 + (6 * 2 + 2x * 2) = -4(x + 3)
6x + -6 + (12 + 4x) = -4(x + 3)

Reorder the terms:
-6 + 12 + 6x + 4x = -4(x + 3)

Combine like terms: -6 + 12 = 6
6 + 6x + 4x = -4(x + 3)

Combine like terms: 6x + 4x = 10x
6 + 10x = -4(x + 3)

Reorder the terms:
6 + 10x = -4(3 + x)
6 + 10x = (3 * -4 + x * -4)
6 + 10x = (-12 + -4x)

Solving
6 + 10x = -12 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
6 + 10x + 4x = -12 + -4x + 4x

Combine like terms: 10x + 4x = 14x
6 + 14x = -12 + -4x + 4x

Combine like terms: -4x + 4x = 0
6 + 14x = -12 + 0
6 + 14x = -12

Add '-6' to each side of the equation.
6 + -6 + 14x = -12 + -6

Combine like terms: 6 + -6 = 0
0 + 14x = -12 + -6
14x = -12 + -6

Combine like terms: -12 + -6 = -18
14x = -18

Divide each side by '14'.
x = -1.285714286

Simplifying
x = -1.285714286

See similar equations:

| 7x-4+66=180 | | 4[x-8]=3x+5 | | (x-4)=(x+7) | | z+66=180 | | 30-4(6)= | | 2(4-3x)-3(2x+1)=7(5x+2)-103 | | 254=139-y | | 4a^3bx-4bx= | | tan(-x)=5/8 | | 8(0+2y)=16(30-4y) | | 9/-4=-2 | | 8x-34+118=180 | | 6x-0=-16 | | 0.5x-0.4y=2.6 | | -0.75+0.4= | | m^2+23m+24=1 | | 2(r+-130)+2r=1660 | | 3y+15x=24 | | 0.2x+0.3y=1.5 | | 5x+2(x-1)=6x-2 | | 3(r+-180)+3r=2340 | | -6f=-20 | | 3(r+-180)+4r=2340 | | a^3-6a^2= | | 16/9=x2 | | 20+6= | | 7x/3= | | M/3-4=12 | | 6m+10-10= | | 5-z=-5 | | 6m+3t+4-4m-2t= | | H=8+17 |

Equations solver categories